3D printing of porous alginate/gelatin hydrogel scaffolds and their mechanical property characterization. Issue 6 (13th April 2017) - You, Fu; Wu, Xia; Chen, Xiongbiao
ABSTRACT: Hydrogel scaffolds with well-defined internal structure and interconnected porosity are important for tissue engineering. A three-dimensional bioplotting technique supplemented with thermal/submerged ionic crosslinking process was used to fabricate hydrogel scaffolds. Six scaffold geometries were fabricated and their influence on mechanical performance was investigated. The 0/90–0.8 group with the lowest porosity showed the highest Young's modulus while the Shift group showed the lowest Young's modulus. Same trend has also been observed for the dynamic modulus of each group. Results demonstrated that the mechanical performance of hydrogel scaffolds can be tuned by changing the internal structure parameters including strands orientation and spacing between strands. GRAPHICAL ABSTRACT: